2011
DOI: 10.1071/ah10885
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for internship: a survey of new interns in a large Victorian Health Service

Abstract: Objective. To gain better understanding of the work-preparedness of new interns and identify areas where further training and education should be provided. Design. Surveys of new interns assessing self-reported confidence and preparedness for tasks commonly undertaken without direct supervision. The first survey was undertaken before the cohort had started work, the second once they had completed their second intern rotation. Setting. A large metropolitan Victorian health service. Participants. All inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 6 publications
2
46
0
Order By: Relevance
“…However, the transition from medical student to junior doctor is a significant one and there is evidence from multiple countries that many commencing interns feel ill-prepared to deal with their new responsibilities [4-11]. Areas of particular concern in relation to intern preparedness appear to vary somewhat between jurisdictions, but include: clinical decision making [4,6,8], the management of emergencies [4,6,7,9,11], communication of difficult news [6,7,10], and the performance of practical procedures [4,7,9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transition from medical student to junior doctor is a significant one and there is evidence from multiple countries that many commencing interns feel ill-prepared to deal with their new responsibilities [4-11]. Areas of particular concern in relation to intern preparedness appear to vary somewhat between jurisdictions, but include: clinical decision making [4,6,8], the management of emergencies [4,6,7,9,11], communication of difficult news [6,7,10], and the performance of practical procedures [4,7,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Hilmer’s group reported that Australian graduates from multiple medical schools appear, both subjectively and objectively, to be poorly equipped for this task, giving rise to real concern about patient safety [12]. These findings were echoed in several of the recent broader studies of intern preparedness from other settings [4,9,10,13], as well as earlier specific prescribing studies by Pearson and colleagues [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…26,27,36-38 However, the best pedagogical approach for preparing medical students to enter into this role is not known. As such, we compared 3 training curricula for preparing medical students to assess and manage a patient with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite few opportunities to acquire the skills needed to effectively engage in acute care, newly graduated doctors are commonly left to manage potentially unstable patients with complex medical conditions 2 3. Lack of experience and confidence in managing acutely unstable patients is a significant source of anxiety for newly graduated medical staff, and studies show that graduating medical students often feel inadequately prepared for emergencies,4 resuscitation5 and the assessment of unstable patients 6 7…”
Section: Introductionmentioning
confidence: 99%